Mitochondrial DNA, Mitochondria, Disease and Stem Cells 2012
DOI: 10.1007/978-1-62703-101-1_4
|View full text |Cite
|
Sign up to set email alerts
|

From Oocytes and Pluripotent Stem Cells to Fully Differentiated Fates: (Also) a Mitochondrial Odyssey

Abstract: In the pluripotent cellular state, characteristic of preimplantation embryos and embryonic stem cells (ESCs), metabolic activity in general, and mitochondrial function in particular, seems to be subdued; increasing upon differentiation, possibly to avoid oxidative stress-mediated damage. A crucial but overlooked aspect of development is related to how mitochondrial differentiation follows somatic differentiation in terms of producing specific cell fates with very distinct metabolic profiles and energy requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…Interestingly, putative substrate availability does not fully explain the differences encountered in the testis, as spermatogonia on the basal membrane remain mostly glycolytic although they are closer to blood vessels (and therefore oxygen sources), while spermatocytes in the seminiferous tubules seem to rely more on OXPHOS, despite being farther away from the oxygen supply. This seems to be a peculiarity spermatogonia share with other stem cells (Ramalho-Santos and Rodrigues, 2013;Ramalho-Santos et al, 2009).…”
Section: Mitochondria In Spermatogenesismentioning
confidence: 84%
See 1 more Smart Citation
“…Interestingly, putative substrate availability does not fully explain the differences encountered in the testis, as spermatogonia on the basal membrane remain mostly glycolytic although they are closer to blood vessels (and therefore oxygen sources), while spermatocytes in the seminiferous tubules seem to rely more on OXPHOS, despite being farther away from the oxygen supply. This seems to be a peculiarity spermatogonia share with other stem cells (Ramalho-Santos and Rodrigues, 2013;Ramalho-Santos et al, 2009).…”
Section: Mitochondria In Spermatogenesismentioning
confidence: 84%
“…Moreover, although previously mitochondria were thought to have a fixed and individual morphology, it is now known that changes in shape (both in terms of cristae structure and matrix texture), size (regulated by the fission/fusion machinery) and relationships with other cellular features (the cytoskeleton, the endoplasmic reticulum) can have important functional consequences (Bereiter-Hahn and Voth, 1994;Collins et al, 2002;Rowland and Voeltz, 2012). Indeed, studies of mitochondrial (dys)function related to aging, degenerative and metabolic disorders or cancer encompass several of these aspects, from abnormal OXPHOS activity and ROS production, to defective apoptosis and mitophagy/autophagy, to changes in mtDNA and mitochondrial structure (Amaral et al, 2008b;Cereghetti and Scorrano, 2011;Correia et al, 2012;Dorn and Scorrano, 2010;Martinou and Youle, 2011;Nunnari and Suomalainen, 2012;Oettinghaus et al, 2012;Palmeira and Ramalho-Santos, 2011;Ramalho-Santos and Rodrigues, 2013;Ramalho-Santos et al, 2009;St John et al, 2010). In short, mitochondria are involved in many other duties while (also) making ATP.…”
Section: Introductionmentioning
confidence: 99%
“…Only later during differentiation, O 2 levels rise and an increase in mitochondria number is accompanied by a shift towards oxidative phosphorylation respiration. 177,179 Indeed, it was shown that cellular differentiation of ESCs and iPSCs depends on OXPHOS and is hampered by the inhibition of CoI or CoIII. [180][181][182] In line with these findings, we have shown that abnormalities in mitochondrial function are associated with a failure of SCZ-derived iPSCs to differentiate into dopaminergic and glutamatergic neurons.…”
Section: The Oxphos In Neuronal Development and Plasticitymentioning
confidence: 99%